(untitled) (Journal of Statistics on Health Decision, 2023)
Background/Objective: Amblyopia is one of the leading causes of monocular vision loss in children in Portugal, affecting 1 to 4% of children. Diagnosis and treatment of amblyopia at an early stage can prevent visual impairment, and thus the Children’s Eye Defects Screening (CEDS) was implemented in primary care health centres nationwide with the aim to identify children with eye changes capable of causing amblyopia.The primary objectives of this study were to compare the proportion of screenings conducted in the different municipalities and the possible interference of the typology of functional units in adherence to screening. Methods: An exploratory analysis using R Software was performed on the standardised screening data to identify differences between the 11 primary care health centres in the Region of Aveiro. In addition, an inferential analysis was performed using non-parametric tests such as the Kruskal-Wallis test and the Wilcoxon test, both used to verify whether there are significant differences between the analysed groups. Results: It is possible to observe that the results obtained in 2021 were abnormal because of the COVID-19 pandemic, which lead to an increase in the number of screenings in 2022. The family health units had higher numbers of requests generated, screening attendances, and reports than personalised health care units, especially in 2021 and 2022. Most of the screening results were negative, with approximately 10% of screenings being positive and roughly 1% of scans being inconclusive. There also appears to be a growing trend of positive results in some municipalities, which may result from a higher reach to the target population of this screening. Conclusions: The purpose of our statistical analysis was to identify differences between the primary health centres in Region of Aveiro. Our results show that might be useful to perform further studies in order to address potential inequities regarding CEDS access.